Flood Damage Assessment: A Review of Flood Stage-Damage Function Curve - Noor Suraya, Romali; Muhammad @ S. A., Kushren Sulaiman; Zulkifli, Yusop; Zulhilmi, Ismail (Springer, 2015)
Nowadays, flood control has been replaced by flood management concept in terms of living with flood, making benefit of it, and minimizing its losses. The success in flood management in any region depends on the evaluation of different types of flood losses. For the assessment of flood damages, this requires the use of stage–damage functions for different categories of land use. A review is presented of the methods used to construct stage–damage function curves for residential, commercial, agricultural, and industrial category. Two main approaches in constructing stage–damage functions are empirical approach, which is based on damage data of past floods, and synthetic approach, which uses damage data collected by interview survey or questionnaire. For a developing country like Malaysia which has limited history and actual flood damage data, the synthetic method is the preferred approach in constructing stage–damage function curve.